2018
DOI: 10.3390/ijms19051470
|View full text |Cite
|
Sign up to set email alerts
|

Silver Nanoparticles: Two-Faced Neuronal Differentiation-Inducing Material in Neuroblastoma (SH-SY5Y) Cells

Abstract: We have previously demonstrated the potential of biologically synthesized silver nanoparticles (AgNP) in the induction of neuronal differentiation of human neuroblastoma, SH-SY5Y cells; we aimed herein to unveil its molecular mechanism in comparison to the well-known neuronal differentiation-inducing agent, all-trans-retinoic acid (RA). AgNP-treated SH-SY5Y cells showed significantly higher reactive oxygen species (ROS) generation, stronger mitochondrial membrane depolarization, lower dual-specificity phosphat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 91 publications
(102 reference statements)
0
7
0
Order By: Relevance
“…In vitro cytotoxicity studies are often used to characterize the biological response to AgNPs, and the results of these studies may be used to identify hazards associated with exposure to AgNPs. Some important studies that have shown the toxic effects of AgNPs on different cell lines, including macrophages (RAW 264.7), including bronchial epithelial cells (BEAS-2B), alveolar epithelial cells (A549), hepatocytes (C3A, HepG2), colon cells (Caco2), skin keratinocytes (HaCaT), human epidermal keratinocytes (HEKs), erythrocytes, neuroblastoma cells, embryonic kidney cells (HEK293T), porcine kidney cells (Pk 15), monocytic cells (THP-1), and stem cells [20,[108][109][110][111][112][113][114][115][116][117], are discussed below.…”
Section: In Vitro Effectsmentioning
confidence: 99%
“…In vitro cytotoxicity studies are often used to characterize the biological response to AgNPs, and the results of these studies may be used to identify hazards associated with exposure to AgNPs. Some important studies that have shown the toxic effects of AgNPs on different cell lines, including macrophages (RAW 264.7), including bronchial epithelial cells (BEAS-2B), alveolar epithelial cells (A549), hepatocytes (C3A, HepG2), colon cells (Caco2), skin keratinocytes (HaCaT), human epidermal keratinocytes (HEKs), erythrocytes, neuroblastoma cells, embryonic kidney cells (HEK293T), porcine kidney cells (Pk 15), monocytic cells (THP-1), and stem cells [20,[108][109][110][111][112][113][114][115][116][117], are discussed below.…”
Section: In Vitro Effectsmentioning
confidence: 99%
“…Interestingly, the AgNPs-intoxicated rats treated with rutin significantly reversed the effect of AgNPs [83]. Dayem et al (2018) [84] observed that AgNPs-treated cells displayed significantly decreased expression of SOD2 and CAT , but no significant effects on GPX expression. In contrast, RA-exposed cells increase the level of antioxidant enzymes, such as SODs , CAT , and GPX4 in SH-SY5Y cells [84].…”
Section: Resultsmentioning
confidence: 99%
“…Dayem et al (2018) [84] observed that AgNPs-treated cells displayed significantly decreased expression of SOD2 and CAT , but no significant effects on GPX expression. In contrast, RA-exposed cells increase the level of antioxidant enzymes, such as SODs , CAT , and GPX4 in SH-SY5Y cells [84]. Collectively, all these studies demonstrate that HN could protect redox imbalance induced by AgNPs.…”
Section: Resultsmentioning
confidence: 99%
“…It would be important to determine the contribution of DUSP1 mRNA transcription to increasing DUSP1 levels in SH-SY5Y cells during long-term H 2 O 2 treatment. In this regard, treatment of SH-SY5Y cells with silver nanoparticles (AgNP) inducing neuronal differentiation increased reactive oxygen species (ROS) generation, which was accompanied by decreased mRNA levels in several DUSPs, including DUSP1, and increased pAKT and pERK1/2 levels [ 61 , 123 ]. In addition, carbachol treatment of SH-SY5Y cells resulted in rapid ERK1/2 activation and increased nuclear DUSP1 protein content [ 62 ], whereas long-term stimulation with the differentiating agent RA caused up-regulation of DUSP1 mRNA in SMS-KCNR NB cells, but not in SH-SY5Y cells [ 67 ].…”
Section: Dusps In Nb Cell Growth and Differentiationmentioning
confidence: 99%